THE SIGNIFICANCE OF THE USAGE OF DISCUSSION METHOD AMONG UNIVERSITY STUDENTS - Z.O. Murodullayeva (American Journals, 2023)
This article provides information about the need to effectively use interactive methods in order to develop communicative competence in the teaching of foreign languages. It is also devoted to the issues of forming the debate method among university students and improving their oral speech competence.
Keywords: method, discussion, comprehension, problem-solving, social interaction, perspective taking